2016
DOI: 10.14202/vetworld.2016.1471-1477
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and discrimination of low doses of Toxocara spp. from public areas soil inferred by loop-mediated isothermal amplification assay as a field-friendly molecular tool

Abstract: Abstract:Aim: One of the main diagnostic problems of conventional polymerase chain reaction (PCR) is indiscrimination of low parasitic loads in soil samples. The aim of this study is to determine the genetic diversity and identification of Toxocara spp. from public areas soil inferred by loop-mediated isothermal amplification (LAMP) assay.Materials and Methods:A total of 180 soil samples were collected from various streets and public parks of northwest Iran. The DNA of recovered Toxocara eggs were extracted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
2
17
0
3
Order By: Relevance
“…Similar to the results of the present study, no difference was found between the results of the microscopic method and 2qPCR technique, a speci c and rapid duplex quantitative real-time PCR on the ITS-2 gene of Toxocara that was used by Durant et al 2012 to detect T. cati and T. canis in soil and feces samples [8]. In a study by Ozlati et al 2016 in Tabriz city, Northwest Iran, 180 samples of suspected contaminated soil were studied using microscopic, PCR and LAMP methods. Based on the results, 57, 14 and 77 samples were detected positive for Toxocara by microscopy, PCR and LAMP methods respectively, of which 49 samples (27.2%) were contaminated with T. cati and 28 samples (15.5%) were contaminated with T. canis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to the results of the present study, no difference was found between the results of the microscopic method and 2qPCR technique, a speci c and rapid duplex quantitative real-time PCR on the ITS-2 gene of Toxocara that was used by Durant et al 2012 to detect T. cati and T. canis in soil and feces samples [8]. In a study by Ozlati et al 2016 in Tabriz city, Northwest Iran, 180 samples of suspected contaminated soil were studied using microscopic, PCR and LAMP methods. Based on the results, 57, 14 and 77 samples were detected positive for Toxocara by microscopy, PCR and LAMP methods respectively, of which 49 samples (27.2%) were contaminated with T. cati and 28 samples (15.5%) were contaminated with T. canis.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the results, 57, 14 and 77 samples were detected positive for Toxocara by microscopy, PCR and LAMP methods respectively, of which 49 samples (27.2%) were contaminated with T. cati and 28 samples (15.5%) were contaminated with T. canis. The results of Ozlati and colleagues showed a higher sensitivity of the LAMP technique than the PCR and microscopy methods [36].…”
Section: Discussionmentioning
confidence: 97%
“…Few authors who detected Toxocara spp. in the environment used molecular methods [ 54 , 55 ]. Ozlati [ 55 ] determined the genetic diversity from soils in public areas, identifying T. canis in 15.5%, T. cati in 27.2%, and mixed infections in 12.2%.…”
Section: Discussionmentioning
confidence: 99%
“…in the environment used molecular methods [ 54 , 55 ]. Ozlati [ 55 ] determined the genetic diversity from soils in public areas, identifying T. canis in 15.5%, T. cati in 27.2%, and mixed infections in 12.2%. Similarly, Khademvatan [ 53 ] identified T. cati more often than T. canis (28% and 5.7% respectively), and no mixed contamination was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Значну кількість робіт учених-паразитологів, представлених у літературних джерелах, присвячено поширенню токсокарозу в країнах Європи та в Україні (Rubinsky-Elefant et al, 2011;Bodnia, 2016;Ozlati et al, 2016;Noor et al, 2019). Так, середня інтенсивність контамінації ґрунтів яйцями нематод роду Toxocara в різних областях України становить 1,6-10,7 % (Pryima, 2010;Said et al, 2018).…”
Section: вступunclassified